An Investigation of Quality of Life of Head-and-neck Cancer Patients after Tumor Resection and Subsequent Prosthetic Rehabilitation: A Clinical Study - Saee Deshpande; Usha Radke; Neelam Pande (Wolters Kluwer Medknow Publications, 2024)
Background: Head-and-neck cancer and its treatment can decrease the quality of life (QoL) of patients in consequence of the loss of structural and functional integrity of the oro- and nasopharyngeal region. Maxillofacial prosthetic treatment is advised when anatomical structures of the head and neck are not replaceable by living tissue, when recurrence is likely, when radiotherapy is administered, or when fragment of fractured bones are severely displaced. The aim of the study was to examine whether prosthetic rehabilitation of maxillofacial defects affects the QoL of patients using the University of Washington (UW)-QoL. Materials and Methods: This was the prospective interventional study using pre- and post-design using a convenience sampling method. The prosthesis was fabricated as per the clinical situation using heat-polymerized polymethyl methacrylate, maxillofacial silicone, or a combination of both. Results: The overall mean composite QOL score before rehabilitation was 68.05 ± 16.98 and after rehabilitation, it was 73.22 ± 11.28. Chewing and saliva (dryness of the mouth) had the lowest scores (55 ± 9.2, 62 ± 8.6, respectively) among all domains, whereas pain and anxiety had the highest scores (93 ± 3.7, 95 ± 1.5, respectively). The domains of appearance, speech, swallowing, chewing, saliva, and overall QoL showed statistically significant improvements postprosthetic rehabilitation. Conclusions: In the present study and selected population, the subjective analysis using UW-QOL showed that despite altered anatomy following resection and reconstruction, compromised physiology following chemoradiation, the oral cancer patients coped well and adapted to near-normal oral status after prosthetic rehabilitation. This was evident from their improved QOL after 1 month of prosthetic rehabilitation.